A cyanamide silicon-carbon composite material based on CVD nano-silicon and its preparation method, application and battery

By coating the surface of CVD nanosilicon with lithium cyanamide compounds and transition metal cyanamide compounds, the cyanamide silicon carbon composite material is formed, which solves the problems of poor rate performance of silicon-based anode materials and low Coulomb efficiency for the first time, and achieves high specific capacity, rate performance and cyclic stability.

CN119340380BActive Publication Date: 2025-04-01SHANGHAI LIHUANG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411885440.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-01
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have poor rate performance and low first-time Coulomb efficiency in lithium-ion batteries, resulting in rapid capacity decay and poor cycle stability.

Method used

Using CVD nanosilicon-based cyanamide silicon carbon composite material, the lithium-ion and electron transport performance are enhanced and lithium storage capacity is improved by coating the nanosilicon surface with lithium-ion and transition metal cyanamide compounds.

Benefits of technology

It significantly improves the specific capacity, rate performance and first-time Coulomb efficiency of the silicon-based anode material, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340380B_ABST
    Figure CN119340380B_ABST
Patent Text Reader

Abstract

The present invention discloses a cyanamide silicon-carbon composite material based on CVD nano-silicon, and a preparation method, application and battery thereof. The preparation method comprises the following steps: (1) mixing a lithium metal cyanamide compound, nano-silicon prepared based on a CVD method and a binder to obtain a composite material A; (2) mixing the composite material A, a transition metal cyanamide compound and a carbon source and granulating the mixture to obtain the cyanamide silicon-carbon composite material based on CVD nano-silicon. The cyanamide silicon-carbon composite material based on CVD nano-silicon prepared by the present invention has excellent specific capacity, rate performance and first effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a cyanamide silicon-carbon composite material based on CVD nano-silicon, a preparation method thereof, an application thereof and a battery. Background Art

[0002] The theoretical specific capacity of silicon to lithium ranks among the top common negative electrode materials, at 4200 mAh / g (Li 22 Si 5 ), and the operating potential of silicon is moderate (~0.4 V vs Li + / Li), so it is generally believed that "silicon-based negative electrode" is the current technical route to replace graphite to solve the problem of high energy density of lithium batteries. However, the silicon-based negative electrode will undergo a huge volume change (>300%) during the alloying process with lithium. This huge volume expansion and contraction will cause the electrode to pulverize and the active material to fall off, causing the capacity of the lithium-ion battery to decay rapidly. The problem of poor cycle stability is particularly significant. Therefore, it is generally necessary to develop new coating methods to meet the application needs of silicon negative electrodes.

[0003] Conventional silicon negative electrode coating methods usually use carbon materials for coating, such as Chinese patent documents CN102394287A and CN105762360A, which respectively develop graphene and natural graphite silicon negative electrode coating methods, effectively improving the cycle life of silicon negative electrodes. However, the ion and electron transmission performance of the silicon negative electrode itself is poor, making it difficult to achieve high-rate charge and discharge; and the side reaction between silicon and the electrolyte consumes lithium, which can easily lead to a significant reduction in the first coulomb efficiency. Therefore, it is urgent to develop a new coating method to meet the application requirements of high first efficiency and high rate of silicon negative electrode materials. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the problems of poor rate performance and low first coulombic efficiency of silicon negative electrode materials in the prior art, and provide a cyanamide silicon-carbon composite material based on CVD nano-silicon and its preparation method, application and battery. The cyanamide silicon-carbon composite material based on CVD nano-silicon prepared by the present invention has excellent specific capacity, rate performance and first efficiency.

[0005] The present invention first coats the surface of nano-silicon prepared based on CVD with a lithium-cyanamide compound, which can enhance the lithium ion transmission capacity of the silicon interface, greatly improve the rate performance of the silicon negative electrode, reduce electrolyte contact and side reactions, and jointly improve the first coulomb efficiency through the lithium supplementation effect; then the high-rate lithium storage capacity is additionally increased by coating the transition metal cyanamide compound on the outer layer. The cyanamide silicon-carbon composite material based on CVD nano-silicon prepared by the present invention contains a metal cyanamide compound, which has a spacious crystal structure, which is conducive to rapid ion diffusion, and the electron conjugated anion promotes the effective transmission of electrons in the crystal structure to improve the rate performance; and the metal cyanamide compound has a relatively spacious crystal structure, which can provide a larger storage / lithium sodium space and transport channel, and enhance the lithium / sodium storage performance of the silicon-based negative electrode. In addition, the lithium metal cyanamide compound fixed on the surface of the silicon source can also serve as a lithium ion conductor and lithium supplement, improving the rate performance of the material, and the transition metal cyanamide compound can provide a theoretical specific capacity far greater than the embedding reaction through the multi-electron redox reaction mechanism of the metal cation, thereby improving the overall high-rate specific capacity of the negative electrode material.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a method for preparing a cyanamide silicon-carbon composite material based on CVD nano-silicon, which comprises the following steps:

[0008] (1) mixing a lithium metal cyanamide compound, nano-silicon prepared by a CVD method, and a binder to obtain a composite material A;

[0009] (2) The composite material A, the transition metal cyanamide compound and the carbon source are mixed and granulated to obtain the cyanamide silicon-carbon composite material based on CVD nano-silicon.

[0010] In step (1), the chemical formula of the lithium metal cyanamide compound can be Li 2 NCN and / or Li 2 M(CN 2 ) 3 , the metal M is one or more of Ti, Sn, Ge, Mn, Si and Zr.

[0011] When the chemical formula of the lithium metal cyanamide compound is Li 2 When NCN is used, the method for preparing the lithium metal cyanamide compound preferably comprises the following steps: under the protection of an inert gas, 3 N and C 3 H 6 N 6 The mixture is heated to 500-700°C and then cooled immediately. 3 N and C 3 H 6 N6 The mass ratio of can be 1: (1.8-2.1), for example 1: 2. The inert gas can be conventional in the art, such as argon. The rate of heating to 500-700°C can be 2-10°C / min, for example 5°C / min. The Li 3 N and C 3 H 6 N 6 The method for preparing the mixture preferably comprises: in a glove box, 3 N and C 3 H 6 N 6 The cooling may be performed by natural cooling to room temperature.

[0012] When the chemical formula of the lithium metal cyanamide compound is Li 2 M(CN 2 ) 3 When the lithium metal cyanamide compound is prepared, the method preferably comprises the following steps: 2 CN 2 The mixture with a metal salt containing M is sealed in a quartz tube and calcined at 400-700° C. for 12-36 hours. The metal salt containing M may be one or more of the hydrochloride, nitrate and sulfate of metal M, such as hydrochloride. 2 CN 2 The molar ratio of the metal salt containing M is generally stoichiometrically added according to the chemical formula of the lithium metal cyanamide compound. The calcination temperature is preferably 50-600° C., such as 550° C. The calcination time is preferably 24-36 hours, such as 24 hours.

[0013] In step (1), the nano-silicon prepared by the CVD method generally refers to nano-silicon prepared by the CVD method. The morphology of the nano-silicon prepared by the CVD method may be silicon nanowires or silicon nanosheets. When the morphology of the nano-silicon prepared by the CVD method is silicon nanowires, the diameter of the silicon nanowires may be 3 to 100 nm; the length of the silicon nanowires may be 0.5 to 20 μm. When the morphology of the nano-silicon prepared by the CVD method is silicon nanosheets, the thickness of the silicon nanosheets may be 3 to 10 nm.

[0014] In step (1), when the morphology of the nano-silicon prepared by the CVD method is silicon nanowires, the method for preparing the silicon nanowires preferably comprises the following steps: performing high-temperature vapor deposition of silane at 400-700° C. on a silicon wafer or a ceramic wafer coated with a gold film on the surface.

[0015] Wherein, the high temperature vapor deposition is generally carried out in a tube furnace. In the process of the high temperature vapor deposition, the silicon wafer or ceramic wafer with a gold film on the surface is generally placed in a tube furnace as a carrier for holding the product, and the gold film is heated to generate a gold nanoparticle catalyst, and the silane is pyrolyzed, deposited and grown into the target product under the action of the catalyst. In the silicon wafer or ceramic wafer with a gold film on the surface, the thickness of the gold film can be 5~10nm. The preparation method of the silicon wafer or ceramic wafer with a gold film on the surface can be conventional in the art, preferably including the following steps: evaporating the silicon wafer or ceramic wafer in a thermal evaporator. The size of the silicon wafer or ceramic wafer can be customized according to the size of the tube furnace cavity, and generally can be placed in the tube furnace cavity. The silicon wafer or ceramic wafer generally needs to be cleaned with an organic solvent (such as ethanol and / or acetone) before use.

[0016] The temperature of the high temperature vapor deposition is preferably 500-600°C, such as 500°C, 550°C or 600°C. The time of the high temperature vapor deposition may be 0.5-4h, such as 1h or 2h. The rate of heating to the temperature of the high temperature vapor deposition may be 10-20°C / min, such as 15°C / min. During the high temperature vapor deposition, the flow rate of silane may be 0.2-2sccm, such as 0.5 sccm or 1 sccm. According to the conventional art, before the high temperature vapor deposition, the reactor is generally evacuated to 10 -4 Pa, then introduce inert gas (such as argon) for 5 to 20 minutes (for example, 10 minutes), and then introduce silane, and stabilize the gas pressure in the reactor at about 50Pa.

[0017] In step (1), when the morphology of the nano-silicon prepared by the CVD method is silicon nanosheets, the method for preparing the silicon nanosheets preferably comprises the following steps: subjecting a mixed gas containing hydrogen and silicon chloride to high-temperature vapor deposition at 800-1200°C.

[0018] Among them, the high-temperature vapor deposition is generally carried out in a tubular furnace. During the high-temperature vapor deposition process, a silicon wafer or a ceramic wafer is generally placed in a tubular furnace as a carrier for holding the product, and the silicon-containing substance is pyrolyzed, deposited and grown on the surface of the carrier to form the target product. The silicon wafer or ceramic wafer generally needs to be cleaned with an organic solvent (such as ethanol and / or acetone) before use. The temperature of the high-temperature vapor deposition may be 900~1100°C, for example, 900°C, 1000°C, 1050°C or 1100°C. The time of the high-temperature vapor deposition may be 0.5~4h, for example, 1h or 2h. The rate of heating to the temperature of the high-temperature vapor deposition may be 10~20°C / min, for example, 15°C / min. During the high-temperature vapor deposition process, the flow rate of hydrogen may be 20~100 sccm, for example, 50 sccm or 80 sccm. According to the convention in the art, before the high-temperature vapor deposition, the reactor is generally evacuated to 10 -4 Below Pa, hydrogen is introduced at a flow rate of 500-3000 sccm (eg, 1000 sccm, 2000 sccm or 2500 sccm) for 5-20 min (eg, 10 min).

[0019] Preferably, the mixed gas containing hydrogen and silicon chloride is introduced after the temperature is raised to the temperature of the high temperature vapor deposition.

[0020] The method of introducing the mixed gas containing hydrogen and silicon chloride preferably includes the following steps: introducing hydrogen into silicon chloride at an introduction flow rate of 20-100 sccm, and discharging it from the silicon chloride liquid by bubbling to obtain the mixed gas containing hydrogen and silicon chloride. The volume of the silicon chloride can be 200-1000 mL.

[0021] In step (1), the mass ratio of the nano-silicon prepared by CVD method to the lithium metal cyanamide compound can be 100:(1-25), for example, 100:5, 100:8, 100:10, 100:15 or 100:20, preferably 100:(3-15).

[0022] In the present invention, according to the common practice in the art, the binder generally refers to a substance that can tightly connect two or more materials together.

[0023] In step (1), the binder preferably includes one or more of sodium carboxymethyl cellulose, polyacrylic acid, polyethylene glycol, polyvinyl pyrrolidone and chitosan, such as polyvinyl pyrrolidone.

[0024] In step (1), the mass ratio of the nano-silicon prepared by CVD method to the binder is preferably 100:(1-10), more preferably 100:(1-5), for example 100:3.

[0025] In step (1), according to the common practice in the art, a solvent is generally added during the mixing.

[0026] The solvent may be one or more of deionized water, ethanol, methanol, isopropanol and acetone.

[0027] Wherein, the mass ratio of the binder to the solvent may be 1:(0.2-5), for example 1:1.

[0028] In step (1), the mixing method can be conventional in the art, such as grinding. The mixing is generally performed under the protection of an inert gas. The mixing time can be 5-30 minutes, such as 10 minutes.

[0029] In some embodiments, the mixing process preferably includes manual grinding for 5-10 minutes, and then ball milling for 5-10 minutes. The rotation speed of the ball mill can be 300-500 rpm, such as 400 rpm.

[0030] In step (1), according to the common practice in the art, the mixing generally needs to be dried.

[0031] In step (2), the chemical formula of the transition metal cyanamide compound may be Q x [NCN] y , wherein Q is a transition metal ion and / or a transition metal oxygen ion, 1≤x≤3, 1≤y≤6.

[0032] Among them, in the transition metal cyanamide compound, Q is preferably one or more of the metal ions and / or metal oxide ions of Sn, Ni, Zr, Nb, Mn, Fe, Ti, Cr, Cu, Co, Zn and Bi, and more preferably one or more of Ni, Sn and Fe.

[0033] In a specific embodiment, the chemical formula of the transition metal cyanamide compound is FeNCN or SnNCN.

[0034] In step (2), the method for preparing the transition metal cyanamide compound preferably comprises the following steps:

[0035] Method 1: Mix the metal salt containing Q with C 3 H 6 N 6 The mixture is calcined at 400-700° C. for 2-5 h under inert gas protection;

[0036] Alternatively, method 2: a metal salt containing Q, C 3 H 6 N 6The mixed solution with the solvent is first subjected to hydrothermal reaction at 120-200° C. for 12-24 hours, washed and dried, and then calcined at 400-700° C. for 2-5 hours under the protection of inert gas.

[0037] In method 1 and / or method 2, the metal salt containing Q may be one or more of basic acetate, hydrochloride, nitrate and sulfate containing Q.

[0038] In method 1 and / or method 2, the metal salt containing Q and C 3 H 6 N 6 The molar ratio may be 1:(1-2), such as 1:1, 1:1.2 or 1:1.58.

[0039] In method 1 and / or method 2, the inert gas may be conventional in the art, such as argon. The rate of heating to the calcination temperature may be 2-10° C. / min, such as 5° C. / min.

[0040] In method 1 and / or method 2, the calcination temperature is preferably 400-600° C., for example 500° C. The calcination time may be, for example, 2 h or 3 h.

[0041] In method 2, the solvent can be conventional in the art, preferably one or more of deionized water, ethanol, methanol and isopropanol, such as methanol.

[0042] In the second method, in the mixed solution, the metal salt containing Q and C 3 H 6 N 6 The sum of the masses of the mixed solution may account for 5%-20%, for example, 10%.

[0043] In method 2, the temperature of the hydrothermal reaction is preferably 160-200° C., such as 180° C. The time of the hydrothermal reaction is preferably 14-20 h, such as 18 h.

[0044] In step (2), the carbon source may be one or more of graphite, carbon nanotubes, pyrolytic carbon, amorphous carbon, hard carbon, soft carbon and carbon black. The graphite may be artificial graphite or natural graphite.

[0045] In step (2), the mass ratio of the composite material A, the transition metal cyanamide compound and the carbon source can be 100:(5-30):(30-110), for example, 100:5:100, 100:10:100, 100:15:100, 100:20:100 or 100:25:100, preferably 100:(10-30):(80-110).

[0046] In step (2), the mixing method can be conventional in the art, such as grinding. The mixing is generally performed under the protection of an inert gas.

[0047] In step (2), according to the conventional art, after the mixing and before the granulation, the composite material A, the transition metal cyanamide compound and the carbon source are generally mixed with a solvent to form a slurry. The solvent can be one or more of deionized water, ethanol and isopropanol, preferably ethanol. The solid content of the slurry can be 40-80%, for example 50%. The solid content generally refers to the percentage of the mass of the solid matter in the slurry to the total mass of the slurry.

[0048] In step (2), the granulation method is preferably spray granulation. The operation and conditions of the spray granulation can be conventional in the art. The process parameters of the spray granulation can be an air inlet temperature of 170-210°C (e.g., 190°C) and an air outlet temperature of 110-140°C (e.g., 120°C).

[0049] The present invention also provides a cyanamide silicon-carbon composite material based on CVD nano-silicon prepared by the preparation method as described above.

[0050] In the present invention, the cyanamide silicon-carbon composite material based on CVD nano-silicon generally has a core-shell structure, with silicon as the core, and a first coating layer and a second coating layer from the inside to the outside; the first coating layer includes a lithium metal cyanamide compound, and the second coating layer includes a transition metal cyanamide compound and a carbon source.

[0051] The present invention also provides an application of the cyanamide silicon-carbon composite material based on CVD nano-silicon as described above in a lithium ion battery or a sodium ion battery.

[0052] The present invention also provides a secondary ion battery, which comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the cyanamide silicon-carbon composite material based on CVD nano-silicon as described above. The secondary ion battery can be a lithium ion battery or a sodium ion battery.

[0053] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0054] The reagents and raw materials used in the present invention are commercially available.

[0055] The positive and progressive effects of the present invention are:

[0056] The cyanamide silicon-carbon composite material based on CVD nano-silicon prepared by the present invention has excellent specific capacity, rate performance and first effect, and the preparation method is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a SEM image of silicon nanowires prepared in the present invention;

[0058] Figure 2 This is a TEM image of the two-dimensional sheet-like nano-silicon prepared by the present invention;

[0059] Figure 3 This is a SEM image of the cyanamide silicon-carbon composite material based on CVD nano-silicon prepared in Example 5;

[0060] Figure 4 is Li in step (1) of Example 1 2 XRD pattern of NCN powder;

[0061] Figure 5 This is the XRD pattern of FeNCN powder in step (2) of Example 1. DETAILED DESCRIPTION

[0062] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0063] The preparation method of the silicon nanowire or two-dimensional sheet-like nanosilicon used in the following examples and comparative examples is as follows:

[0064] Preparation of silicon nanowires by chemical vapor deposition: The surface of the silicon wafer was cleaned with ethanol and acetone in turn, and a 5-10 nm thick gold film was deposited on the surface using a thermal evaporator to prepare a carrier. The carrier was placed in a tube furnace and evacuated to 10 -4 Pa, after introducing 200 sccm high-purity argon for 10 min, the introduction of argon was stopped and replaced with 0.5 sccm silane to stabilize the gas pressure of the tube furnace at about 50 Pa. The temperature of the tube furnace was increased to 550°C at a heating rate of 15°C / min, and after maintaining for 1 h, the introduction of silane was stopped and the temperature was lowered to obtain silicon nanowires.

[0065] Preparation of two-dimensional nano-silicon sheets by chemical vapor deposition: The surface of the silicon wafer was cleaned with ethanol and acetone in turn, and then placed in a tube furnace and evacuated to 10 -4 Pa, after introducing 2000sccm high-purity hydrogen for 10 minutes, the temperature of the tube furnace was increased to 1050°C at a heating rate of 15°C / min, and 500mL of silicon chloride (purity 99.999%) was introduced into the tube furnace by bubbling with hydrogen at a flow rate of 50sccm as a carrier gas. After maintaining for 1 hour, the reaction was terminated and the temperature was lowered to obtain two-dimensional flaky nanosilicon.

[0066] Example 1

[0067] Step (1): Weigh Li in a glove box at a mass ratio of 1:2.3 N and C 3 H 6 N 6 The powder was evenly ground and loaded into a porcelain boat; the porcelain boat containing the raw material powder was taken out of the glove box and quickly transferred to a tube furnace, and an argon atmosphere was introduced for protection. The temperature was increased to 600°C at a heating rate of 5°C / min and then naturally cooled to room temperature to obtain an off-white Li 2 NCN powder;

[0068] Li 2 NCN, silicon nanowires, PVP (K30, Sinopharm), and ethanol were evenly ground in a mortar in a mass ratio of 5:100:3:3 in a glove box for 5 min, and then loaded into a nitrogen-protected agate ball mill with a ball-to-material ratio of 25:1. The diameter of a single grinding ball was 10 mm, the ball mill speed was set to 400 rpm, and the ball mill was milled for 5 min and dried to obtain a composite material.

[0069] Step (2): weigh basic iron acetate Fe(OH)(CH 3 COO 2 and C 3 H 6 N 6 After the powder is evenly ground, it is placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min under argon protection. After being kept at this temperature for 2 h, it is naturally cooled to room temperature to obtain FeNCN powder material.

[0070] The composite material prepared in step 1, FeNCN, and artificial graphite (Betray) were uniformly ground in a glove box in a mortar at a mass ratio of 100:15:100 for 10 min, and the mixed sample was prepared into a slurry with a solid content of 50% in ethanol and pumped into a spray granulator. Spray granulation was carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C, and then sieved through a 200-mesh sieve to obtain a cyanamide silicon-carbon composite material.

[0071] Example 2

[0072] Compared with Example 1, except that Li 2 Except that the mass ratio of NCN, silicon nanowires, PVP and ethanol was changed from 5:100:3:3 to 10:100:3:3, other conditions and parameters were the same as those in Example 1.

[0073] Example 3

[0074] Compared with Example 1, except that Li 2 NCN replaced by Li 2 Ti(CN 2 ) 3Except for this, other conditions and parameters are the same as those in Example 1.

[0075] Li 2 Ti(CN 2 ) 3 Preparation method:

[0076] Li 2 CN 2 With TiCl 4 The mixture was mixed evenly in a molar ratio of 3:1, ground evenly, sealed in a quartz tube, kept in a muffle furnace at 550°C for 24 hours, and cooled naturally to obtain Li 2 Ti(CN 2 ) 3 .

[0077] Example 4

[0078] Compared with Example 1, except that FeNCN in step (2) of Example 1 is replaced by SnNCN, other conditions and parameters are the same as those of Example 1.

[0079] The preparation method of SnNCN is:

[0080] SnCl 2 With C 3 H 6 N 6 A methanol solution with a solute mass fraction of 10% was prepared in a molar ratio of 1:1, and the solution was charged into a hydrothermal autoclave and placed in a 180°C oven for 18 hours; the mixture was filtered and dried in a vacuum oven at room temperature for 4 hours, and then the obtained white solid was heated to 500°C at a heating rate of 5°C / min under an argon atmosphere, kept for 3 hours, and then naturally cooled to room temperature to obtain SnNCN.

[0081] Example 5

[0082] Compared with Example 1, except that the silicon nanowires in step (1) of Example 1 are replaced by two-dimensional sheet-like nanosilicon, other conditions and parameters are the same as those of Example 1.

[0083] Example 6

[0084] Compared with Example 1, except that Li 2 Except that the mass ratio of NCN, silicon nanowires, PVP and ethanol was adjusted from 5:100:3:3 to 20:100:3:3, other conditions and parameters were the same as those in Example 1.

[0085] Example 7

[0086] Compared with Example 1, except that the mass ratio of the composite material, FeNCN and artificial graphite in step (2) of Example 1 is adjusted from 100:15:100 to 100:5:100, other conditions and parameters are the same as those of Example 1.

[0087] Example 8

[0088] Compared with Example 1, except that the mass ratio of the composite material, FeNCN and artificial graphite in step (2) of Example 1 is adjusted from 100:15:100 to 100:25:100, other conditions and parameters are the same as those of Example 1.

[0089] Example 9

[0090] Step (1): Li 2 CN 2 With TiCl 4 The mixture was mixed evenly in a molar ratio of 3:1, ground evenly, sealed in a quartz tube, kept in a muffle furnace at 550°C for 24 hours, and cooled naturally to obtain Li 2 Ti(CN 2 ) 3 ;

[0091] Li 2 Ti(CN 2 ) 3 , silicon nanowires, PVP (K30, Sinopharm) and ethanol were evenly ground in a mortar in a mass ratio of 10:100:3:3 in a glove box for 5 min, and then loaded into a nitrogen-protected agate ball mill with a ball-to-material ratio of 25:1. The diameter of a single grinding ball was 10 mm, the ball mill speed was set to 400 rpm, and the ball mill was milled for 5 min and dried to obtain a composite material.

[0092] Step (2): weigh basic iron acetate Fe(OH)(CH 3 COO 2 and C 3 H 6 N 6 After the powder is uniformly ground, it is placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min under argon protection, kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain FeNCN powder material;

[0093] The composite material prepared in step 1, FeNCN, and artificial graphite (Betray) were uniformly ground in a glove box in a mortar at a mass ratio of 100:15:100 for 10 min, and the mixed sample was prepared into a slurry with a solid content of 50% in ethanol and pumped into a spray granulator. Spray granulation was carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C, and then sieved through a 200-mesh sieve to obtain a cyanamide silicon-carbon composite material.

[0094] Example 10

[0095] Compared with Example 9, except that Li 2 Ti(CN 2 ) 3 Replaced by Li 2 Sn(CN 2 ) 3 Except for this, other conditions and parameters are the same as those in Example 9.

[0096] Li 2 Sn(CN 2 ) 3 The preparation method is as follows: Li 2 CN 2 With SnCl 4 The mixture was mixed evenly in a molar ratio of 3:1, ground evenly, sealed in a quartz tube, kept in a muffle furnace at 550°C for 24 hours, and cooled naturally to obtain Li 2 Sn(CN 2 ) 3 .

[0097] Embodiment 11

[0098] Compared with Example 9, except that Li 2 Ti(CN 2 ) 3 Replaced by Li 2 Ge(CN 2 ) 3 Except for this, other conditions and parameters are the same as those in Example 9.

[0099] Li 2 Ge(CN 2 ) 3 The preparation method is as follows: Li 2 CN 2 With GeCl 4 The mixture was mixed evenly in a molar ratio of 3:1, ground evenly, sealed in a quartz tube, kept in a muffle furnace at 550°C for 24 hours, and cooled naturally to obtain Li 2 Ge(CN 2 ) 3 .

[0100] Comparative Example 1

[0101] Step (1): Nano-silicon (Colodex 80-100 nm), PVP (K30, Sinopharm) and ethanol were uniformly ground at a mass ratio of 100:3:3 for 5 min, and then placed in a nitrogen-protected agate ball mill with a ball-to-material ratio of 25:1. The diameter of a single grinding ball was 10 mm, the ball mill speed was set to 400 rpm, and the ball mill was milled for 5 min. The composite material was dried.

[0102] Step (2): After the composite material prepared in step (1) and artificial graphite are uniformly ground at a mass ratio of 100:100 for 10 minutes, the mixed sample is prepared into a slurry with a solid content of 50% in ethanol and pumped into a spray granulator. Spray granulation is carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C to obtain a silicon-carbon composite material.

[0103] Comparative Example 2

[0104] Step (1): Same as Example 1.

[0105] Step (2): After the composite material prepared in step (1) and artificial graphite are uniformly ground at a mass ratio of 100:100 for 10 minutes, the mixed sample is prepared into a slurry with a solid content of 50% in ethanol and pumped into a spray granulator. Spray granulation is carried out under the conditions of an air inlet temperature of 190°C and an air outlet temperature of 120°C to obtain a silicon-carbon composite material.

[0106] Comparative Example 3

[0107] Step (1): Silicon nanowires, PVP (K30, Sinopharm) and ethanol were uniformly ground at a mass ratio of 100:3:3 for 5 min, and then placed in a nitrogen-protected agate ball mill with a ball-to-material ratio of 25:1. The diameter of a single grinding ball was 10 mm, the ball mill speed was set to 400 rpm, and the ball mill was milled for 5 min. The composite material was dried.

[0108] Step (2): Same as Example 1.

[0109] Effect Example

[0110] (1) Morphology and particle size characterization

[0111] Figure 1 This is a SEM image of the silicon nanowire prepared by the present invention. It can be seen from the image that the diameter of the silicon nanowire is 3-100 nm; the length of the silicon nanowire is 0.5-20 μm; Figure 2 This is a TEM image of the two-dimensional sheet-like nano-silicon prepared by the present invention, and its thickness is 3-10nm; Figure 3 This is a SEM image of the cyanamide silicon-carbon composite material based on CVD nano-silicon prepared in Example 5; Figure 4 is Li in step (1) of Example 1 2 NCN powder XRD pattern; Figure 5 This is the XRD pattern of FeNCN powder in step (2) of Example 1.

[0112] (2) Lithium-ion battery electrochemical performance test

[0113] The cyanamide silicon-carbon composite materials based on CVD nano-silicon prepared in Examples 1 to 11 and the silicon-carbon composite materials prepared in Comparative Examples 1-3 were subjected to half-cell tests. The test method is: the above materials are uniformly mixed with a binder CMC (sodium carboxymethyl cellulose) and conductive carbon black in a mass ratio of 80:10:10, adjusted into a slurry, coated on a copper foil with a coating thickness of 100 microns, and dried at 80°C in vacuum for 12 hours to prepare a lithium battery negative electrode sheet. The simulated battery assembly was carried out in an argon-filled glove box, using 1 mol / L LiPF 6 The electrolyte (solvents are EC, DMC and FEC, EC: DMC = 1:1 (volume ratio), FEC accounts for 5% of the total volume of the solvent), polypropylene microporous membrane is used as the separator, and the metal lithium sheet is used as the counter electrode. The electrochemical performance test was carried out on a Land CT2001A battery tester at a temperature of 25°C. The charge and discharge voltage range was 0.01 to 1.5V (1 C=1000 mAh / g). The test results are shown in Table 1.

[0114] Table 1

[0115]

[0116] According to the above experimental results, the cyanamide silicon-carbon composite material based on CVD nano-silicon prepared in the present invention has excellent specific capacity, first coulombic efficiency and cycle performance, especially has better 10 C specific capacity and high rate cycle performance.

[0117] By comparing Example 1 with Comparative Example 1, it can be found that the silicon-carbon composite material prepared in Comparative Example 1, due to the lack of both the lithium-containing cyanamide compound and the transition metal cyanamide compound coating, the overall sample cannot replenish lithium and the ion / electron conductivity is poor, and lithium ions are difficult to fully deintercalate, so the specific capacity, first coulomb efficiency, high-rate capacity and cycle life are poor. By comparing Example 1 with Comparative Example 2, it can be found that the silicon-carbon composite material prepared in Comparative Example 2, due to the lack of transition metal cyanamide compound coating, will reduce some ion / electron conductivity, and lack the high-rate lithium storage capacity of the transition metal cyanamide compound, so the high-rate capacity and cycle life are significantly reduced. By comparing Example 1 with Comparative Example 3, it can be seen that Comparative Example 3 cannot replenish lithium and reduces some ion / electron conductivity due to the lack of lithium-containing cyanamide compound, so it will have a greater impact on the first coulomb efficiency.

[0118] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a cyanamide silicon-carbon composite material based on CVD nano-silicon, characterized in that: The following steps are involved: (1) mixing a lithium metal cyanamide compound, nano-silicon prepared by a CVD method, and a binder to obtain a composite material A; (2) The composite material A, the transition metal cyanamide compound and the carbon source are mixed and granulated to obtain the cyanamide silicon-carbon composite material based on CVD nano-silicon.

2. The method for preparing the cyanamide silicon-carbon composite material based on CVD nano-silicon according to claim 1, characterized in that: Step (1) satisfies one or more of the following conditions: (1) The chemical formula of the lithium metal cyanamide compound is Li2NCN and / or Li2M(CN2)3, and the metal M is one or more of Ti, Sn, Ge, Mn, Si and Zr; (2) The morphology of the nano-silicon prepared by the CVD method is a silicon nanowire or a silicon nanosheet; the diameter of the silicon nanowire is 3 to 100 nm, the length of the silicon nanowire is 0.5 to 20 μm; the thickness of the silicon nanosheet is 3 to 10 nm; (3) The mass ratio of the nano-silicon prepared by the CVD method to the lithium metal cyanamide compound is 100:(1-25); (4) The binder comprises one or more of sodium carboxymethyl cellulose, polyacrylic acid, polyethylene glycol, polyvinyl pyrrolidone and chitosan; (5) The mass ratio of the nano-silicon prepared by the CVD method to the binder is 100:(1-10); (6) A solvent is also added during the mixing; the solvent is one or more of deionized water, ethanol, methanol, isopropanol and acetone.

3. The method for preparing the cyanamide silicon-carbon composite material based on CVD nano-silicon according to claim 2, characterized in that: When the chemical formula of the lithium metal cyanamide compound is Li2NCN, the preparation method of the lithium metal cyanamide compound comprises the following steps: under the protection of an inert gas, heating a mixture of Li3N and C3H6N6 to 500-700°C and then immediately cooling it; Or, when the chemical formula of the lithium metal cyanamide compound is Li2M(CN2)3, the preparation method of the lithium metal cyanamide compound comprises the following steps: sealing a mixture of Li2CN2 and a metal salt containing M in a quartz tube and calcining at 400-700°C for 12-36h; Alternatively, the method for preparing silicon nanowires comprises the following steps: performing high-temperature vapor deposition of silane at 400-700° C. on a silicon wafer or a ceramic wafer coated with a gold film on the surface; Alternatively, the method for preparing the silicon nanosheets comprises the following steps: subjecting a mixed gas containing hydrogen and silicon chloride to high-temperature vapor deposition at 800-1200° C.; Alternatively, the mass ratio of the binder to the solvent is 1:(0.2-5).

4. The method for preparing the cyanamide silicon-carbon composite material based on CVD nano-silicon according to claim 3, characterized in that: The mass ratio of Li3N to C3H6N6 is 1:(1.8-2.1); Or, the molar ratio of Li2CN2 to the metal salt containing M is added in a stoichiometric ratio according to the chemical formula of the lithium metal cyanamide compound; Or, in the method for preparing silicon nanowires, the time of high temperature vapor deposition is 0.5 to 4 hours; Alternatively, in the method for preparing the silicon nanosheets, the time of the high-temperature vapor deposition is 0.5 to 4 hours.

5. The method for preparing the cyanamide silicon-carbon composite material based on CVD nano-silicon according to claim 1, characterized in that: Step (2) satisfies one or more of the following conditions: (1) The chemical formula of the transition metal cyanamide compound is Q x [NCN] y , wherein Q is a transition metal ion and / or a transition metal oxygen ion, 1≤x≤3, 1≤y≤6; (2) The preparation method of the transition metal cyanamide compound comprises the following steps: Method 1: calcining a mixture of a metal salt containing Q and C3H6N6 at 400-700°C for 2-5h under inert gas protection; Alternatively, method 2: a mixed solution of a metal salt containing Q, C3H6N6 and a solvent is first subjected to a hydrothermal reaction at 120-200°C for 12-24h, washed and dried, and then calcined at 400-700°C for 2-5h under inert gas protection; (3) The carbon source is one or more of graphite, carbon nanotubes, hard carbon, soft carbon and carbon black; (4) The mass ratio of the composite material A, the transition metal cyanamide compound and the carbon source is 100:(5-30):(30-110); (5) The granulation is spray granulation.

6. The method for preparing the cyanamide silicon-carbon composite material based on CVD nano-silicon according to claim 5, characterized in that: In the transition metal cyanamide compound, Q is one or more of the metal ions and / or metal oxide ions of Sn, Ni, Zr, Nb, Mn, Fe, Ti, Cr, Cu, Co, Zn and Bi; Alternatively, the process parameters of the spray granulation are an air inlet temperature of 170-210°C and an air outlet temperature of 110-140°C.

7. The method for preparing the cyanamide silicon-carbon composite material based on CVD nano-silicon according to claim 5, characterized in that: In the preparation method of the transition metal cyanamide compound, in method 1 and / or method 2, the molar ratio of the metal salt containing Q to C3H6N6 is 1:(1-2); Or, in method 2, in the mixed solution, the sum of the masses of the metal salt containing Q and C3H6N6 accounts for 5%-20% of the total mass of the mixed solution.

8. A cyanamide silicon-carbon composite material based on CVD nano-silicon obtained by the preparation method of the cyanamide silicon-carbon composite material based on CVD nano-silicon as described in any one of claims 1 to 7.

9. An application of the cyanamide silicon-carbon composite material based on CVD nano-silicon as claimed in claim 8 in lithium-ion batteries or sodium-ion batteries.

10. A secondary ion battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the cyanamide silicon-carbon composite material based on CVD nano-silicon as claimed in claim 8.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material of lithium ion battery and preparation method thereof

    CN102394287A

  • Graphene-silicon-coated composite negative electrode material and preparing method and application thereof

    CN105762360A

  • High-stability silicon-carbon composite negative electrode material as well as preparation method and application thereof

    CN117936753A